Market Share of Faith-Inspired Health Care Providers : Reach to the Poor in Africa - Wodon, Quentin (Taylor and Francis, 2014)
Market share estimates—typically in the 30 percent to 40 percent range—are frequently wielded as the most concrete evidence of faith-inspired activity and impact in the area of health care provision in Sub-Saharan Africa. In fact, there are few speeches, reports, or articles that do not make some mention of market share, attaching some percentage to the significance of faith-inspired healthcare provision in the continent as a whole, or in specific countries. Such statements usually appear in the early stages of a text, and are the basis on which a further argument is made, for example that this sector therefore requires further attention or resources from governments and donors. A systematic review of this literature reveals that these statements have currently reached the point of becoming almost indisputable “truth,” as they are now frequently made without any referencing.